Tendencias de investigación en salud. Análisis y reflexiones (2014)
Objective: Analyze the state of health research in Colombia, Ecuador and Latin America, its implications and the importance of health research in attempting to impact health policies and strategies that will improve the standard of living in urban communities. Method: The study involved a review of the literature contained in the Latin American databases SciELO, Redalyc, Medicine ® and PubMed during the last eight years. Results: It provides evidence on the importance of universities as institutions that are obliged to influence social, human and cultural aspects and become environs linked to social and government program developed in the interest of a community. Research policies, governing bodies and their implications in institutions of higher learning are analyzed as well. Conclusions: It is necessary to strengthen critical thinking in academic circles that are committed to transforming the social conditions of the community in processes concerning health, disease, promotion, prevention and care. In doing to, it is important to affect awareness by affirming that both the individual and the community are responsible for their "health care," through a trans-disciplinary approach that takes into account the ethical standards governing research and strengthens it by consolidating networks and reporting research findings.